2022
DOI: 10.3390/ijms23041940
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Vesicles for Nanoencapsulated Sulforaphane Increased Their Anti-Inflammatory Role on an In Vitro Human Macrophage Model

Abstract: At present, there is a growing interest in finding new non-toxic anti-inflammatory drugs to treat inflammation, which is a key pathology in the development of several diseases with considerable mortality. Sulforaphane (SFN), a bioactive compound derived from Brassica plants, was shown to be promising due to its anti-inflammatory properties and great potential, though its actual clinical use is limited due to its poor stability and bioavailability. In this sense, the use of nanocarriers could solve stability-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 81 publications
2
14
1
Order By: Relevance
“…Nevertheless, in this experimental model, we found no differences between free SFN and SFN in the encapsulated format, probably due to the powerful effect shown by the free compound. These results are consistent with those obtained previously for TNF-α and IL-6 in macrophage-like cell line models with free SFN [ 35 ] or SFN encapsulated in broccoli membrane vesicles [ 30 ], although the effect recorded was less potent. The effect previously described on IL-1β in cell line models could only be detected when SFN was loaded into broccoli membrane vesicles, achieving a 50% decrease relative to controls cells under inflammatory conditions [ 30 ], whereas the results presented in this study showed that both free and encapsulated SFN completely abrogated the effect of IL-1β production of this cytokine in primary cultures of M1 macrophages.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Nevertheless, in this experimental model, we found no differences between free SFN and SFN in the encapsulated format, probably due to the powerful effect shown by the free compound. These results are consistent with those obtained previously for TNF-α and IL-6 in macrophage-like cell line models with free SFN [ 35 ] or SFN encapsulated in broccoli membrane vesicles [ 30 ], although the effect recorded was less potent. The effect previously described on IL-1β in cell line models could only be detected when SFN was loaded into broccoli membrane vesicles, achieving a 50% decrease relative to controls cells under inflammatory conditions [ 30 ], whereas the results presented in this study showed that both free and encapsulated SFN completely abrogated the effect of IL-1β production of this cytokine in primary cultures of M1 macrophages.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with those obtained previously for TNF-α and IL-6 in macrophage-like cell line models with free SFN [ 35 ] or SFN encapsulated in broccoli membrane vesicles [ 30 ], although the effect recorded was less potent. The effect previously described on IL-1β in cell line models could only be detected when SFN was loaded into broccoli membrane vesicles, achieving a 50% decrease relative to controls cells under inflammatory conditions [ 30 ], whereas the results presented in this study showed that both free and encapsulated SFN completely abrogated the effect of IL-1β production of this cytokine in primary cultures of M1 macrophages. These results are also in accordance with previous studies in rats with sciatic endometriosis, where SFN treatment reduced TNF-α, IL-6, and IL-1β.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…P-EVs isolated from broccoli have been found to contain sulforaphane. There have been few reports that suggest it has cancer-protective properties [ 99 ]. P-EVs from grapefruit contain naringenin, fructose, citric acid, glucose, sucrose myo-inositol, quinic acid, oxalic acid, glycolic acids, aucubin in addition to amino acids leucine and isoleucine [ 82 , 91 , 100 ].…”
Section: Biological Composition and Function Of P-evsmentioning
confidence: 99%